1990
DOI: 10.1128/aem.56.10.3216-3219.1990
|View full text |Cite
|
Sign up to set email alerts
|

Thermotolerance of Listeria monocytogenes and Salmonella typhimurium after sublethal heat shock

Abstract: The effect of prior heat shock on thermotolerance of Listeria monocytogenes and Salmonella typhimurium in broth culture was determined. Bacteria were grown at the permissive temperature of 35°C, sublethally heated at 35 (control), 42, 48, and 52°C (nonpermissive control) for various times, and inactivated at either 57.8 or 52°C. The induction of increased thermotolerance by heat shock, although consistent within each experiment, was generally not significant for L. monocytogenes; the increase was significant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(50 citation statements)
references
References 22 publications
5
44
0
1
Order By: Relevance
“…1990). The heat shock proteins appear to increase D values of S. fyphirnuriurn 1 to 2 fold (Mackey and Derrick 1986;Bunning et al 1990). Although we did not analyze for heat shock proteins, their presence may indicate why more than a 5 rnin treatment was needed at 60C to decrease S. typhirnuriurn counts.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…1990). The heat shock proteins appear to increase D values of S. fyphirnuriurn 1 to 2 fold (Mackey and Derrick 1986;Bunning et al 1990). Although we did not analyze for heat shock proteins, their presence may indicate why more than a 5 rnin treatment was needed at 60C to decrease S. typhirnuriurn counts.…”
Section: Resultsmentioning
confidence: 90%
“…It has been shown that heat treatments, such as immersion of carcasses in hot water, poultry carcasses (Dawson et al 1963;Klose and Bayne 1971;Cox et al 1974b: Thomson et al 1976; Thomson et al 1979;Morrison and Fleet 1985). Other end-product treatments which have been proposed for reducing or eliminating salmonellae from poultry carcasses include spray rinsing , air scrubbing (Dikens and Cox 1992), gamma irradiation (Mulder et al 1977, Katta et al 1991, immersion in chlorinated water (Mead et al 1975;Thomson et al 1976) and solutions of various chemicals such as organic acids (Lillard et al 1987;Cox et al 1974a;Juven et al 1974), gluteraldehyde (Thomson et al 1977), sorbates (To and Robach 1980), and trisodium phosphate (Bender 1992).…”
Section: Introductionmentioning
confidence: 99%
“…To have additional margin of safety, combined action of different environmental factors such as pH, water activity, temperature, food composition and physiological state of vegetative cells and spores were studied recently (Knabel et al 1990;Casadei et al 1998;Gnanou Besse et al 2000;Tienungoon et al 2000;Koutsoumanis and Sofos 2005;Fernandez et al 2007;Leguerinel et al 2007). Mathematical models have been proposed to describe and quantify the impact of these environmental factors on L. monocytogenes inactivation resulting from NaCl and temperature treatments (Bunning et al 1990;Linton et al 1992;Membre et al 1997;Augustin et al 1998), pH, NaCl and lactic acid treatments (Tienungoon et al 2000), and modification of water activity (Fernandez et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…E. sakazakii in PIMF could be expected to have been exposed to environmental stresses such as starvation, desiccation and temperature extremes or to different types of detergents and sanitizers in processing plants. Since stress can influence bacterial response to lethal physical treatment (Bunning et al 1990;Leenanon and Drake 2001), it seemed appropriate to consider whether environmental history (prior stress) could influence the irradiation resistance of E. sakazakii.…”
Section: Introductionmentioning
confidence: 99%